Protein tyrosine phosphatase µ (PTP µ or PTPRM), a negative regulator of proliferation and invasion of breast cancer cells, is associated with disease prognosis. - Ping-Hui Sun (Public Library of Science (PLoS), 2012)
Background PTPRM has been shown to exhibit homophilic binding and confer cell-cell adhesion in cells including epithelial and cancer cells. The present study investigated the expression of PTPRM in breast cancer and the biological impact of PTPRM on breast cancer cells. Design Expression of PTPRM protein and gene transcript was examined in a cohort of breast cancer patients. Knockdown of PTPRM in breast cancer cells was performed using a specific anti-PTPRM transgene. The impact of PTPRM knockdown on breast cancer was evaluated using in vitro cell models. Results A significant decrease of PTPRM transcripts was seen in poorly differentiated and moderately differentiated tumours compared with well differentiated tumours. Patients with lower expression of PTPRM had shorter survival compared with those which had a higher level of PTPRM expression. Knockdown of PTPRM increased proliferation, adhesion, invasion and migration of breast cancer cells. Furthermore, knockdown of PTPRM in MDA-MB-231 cells resulted in increased cell migration and invasion via regulation of the tyrosine phosphorylation of ERK and JNK. Conclusions Decreased expression of PTPRM in breast cancer is correlated with poor prognosis and inversely correlated with disease free survival. PTPRM coordinated cell migration and invasion through the regulation of tyrosine phosphorylation of ERK and JNK.